AfSec1 is a signal peptidase and removes signal peptides of 1, 3-β-glucanosyltransferases in Aspergillus fumigatus. (19th January 2023) - Kim, Ki-Hwan; Kang, Suzie; Seo, Hyewon; Yun, Cheol-Won
Abstract: To identify the infection mechanism of Aspergillus fumigatus, which is an opportunistic fungal pathogen, we analyzed the expression profile of the whole genome of A. fumigatus during the infection of murine macrophages. A previously reported RNA-seq data analysis showed that many genes involved in cell wall synthesis were upregulated during the infection process. Interestingly, AfSec1 (3g12840), which encodes a putative signal peptidase, was upregulated dramatically, and its putative target protein Gel1, which encodes a 1, 3-β-glucanosyltransferase, was also upregulated. Instead of the AfSec1 deletion strain, the AfSec1-ΔP strain was constructed, in which the promoter region of AfSec1 was deleted, and AfSec1 expression was not detected in the AfSec1-ΔP strain. The expression of AfSec1 was recovered by the introduction of the promoter region (the AfSec1-ΔP/P strain). The nonprocessed form of Gel1 was identified in the AfSec1-ΔP strain, which lacked the promoter, but mature forms of Gel1 were found in the wild-type and in AfSec1-ΔP/P, which was the promoter complementation strain. In the plate assay, the AfSec1-ΔP strain showed higher sensitivity against caspofungin than the wild-type. However, compared with the wild-type, the deletion strain showed no difference in the sensitivity to other antifungal drugs, such as amphotericin B and voriconazole, which inhibit different targets compared with caspofungin. The AfSec1-ΔP strain exhibited ∼20% lower levels of β-glucan in the cell wall than the wild-type. Finally, the virulence decreased when the promoter region of AfSec1 was deleted, as observed in the murine infection test and conidia-killing assay using human macrophages and neutrophils. These results suggest that AfSec1 exerts signal peptidase activity on its target Gel1 and has an important role in fungal pathogenesis. Lay Summary: We identified the novel signal peptidase AfSec1 from A. fumigatus . AfSec1 which removes the signal peptide of 1, 3-β-glucanosyltransferases, is a virulence factor and is a potential target for a new antifungal drug.